2018
DOI: 10.1111/eip.12540
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary efficacy of a smartphone application intervention for subthreshold depression

Abstract: Although this app intervention has the potential to reduce depressive symptoms, the app needs to be improved to increase adherence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…All studies examined usage data in some aspects of their evaluation, and most papers were ascribed to one or more of the following constructs: user adherence [ 40 , 46 , 49 - 51 , 53 , 55 , 62 , 64 , 75 , 80 , 82 , 85 ], engagement [ 47 , 48 , 52 , 56 , 61 , 65 , 67 , 77 , 79 , 84 ], or acceptability [ 45 , 57 , 71 ]. Although adoption was included in our search, none of the reviewed studies used analytics as a proxy to measure that indicator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies examined usage data in some aspects of their evaluation, and most papers were ascribed to one or more of the following constructs: user adherence [ 40 , 46 , 49 - 51 , 53 , 55 , 62 , 64 , 75 , 80 , 82 , 85 ], engagement [ 47 , 48 , 52 , 56 , 61 , 65 , 67 , 77 , 79 , 84 ], or acceptability [ 45 , 57 , 71 ]. Although adoption was included in our search, none of the reviewed studies used analytics as a proxy to measure that indicator.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of how metrics were analyzed, many studies [ 40 , 42 , 44 - 48 , 50 , 54 , 57 - 59 , 62 , 63 , 65 , 66 , 68 - 70 , 72 - 77 , 79 , 80 , 82 , 85 , 86 ] presented usage metrics separately from the main study data using descriptive methods, which included the overall counts, frequencies, means, or SDs. Several studies [ 39 , 84 ] had the main objective of examining how different interventions (eg, behavioral activation) impacted user engagement on the app.…”
Section: Resultsmentioning
confidence: 99%
“…While no such applications exist for PSD ( Pugliese et al, 2018 ), several have been reported to improve depressive symptoms in patients with clinical depression and subthreshold depression ( Hung et al, 2016 ; Takahashi et al, 2019b ; Ly et al, 2014 ; Ly et al, 2015 ; Fitzpatrick et al, 2017 ). To provide a therapeutic option that is easy to use, less burdensome for patients and caregivers, and with much lower risk of adverse effects, we have developed a motion picture-reproducing application called Subliminal Priming with Supraliminal Reward Stimulation (SPSRS) ( Takahashi et al, 2019b ). The SPSRS application automatically displays positive words in videos to improve depressive symptoms in patients with subthreshold depression.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the SPSRS application is less burdensome for PSD patients and enables the intervention practitioner to perform a unified intervention. Previous studies have shown that the SPSRS application can reduce depressive symptoms in patients with subthreshold depression ( Takahashi et al, 2019b ). However, there are relatively few studies on the mechanisms underlying specific symptoms or clinical features of PSD ( Robinson and Jorge, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, even this rather conservative transition to smartphones has led to interventions out of reach for classic mobile phones. Exploiting larger screen resolutions and multimedia capabilities, one finds examples of multimodal learning materials using both audio and video guides [133,167], using pictures [83, 86-88, 117, 129], audio [83,87,88,117], music [86][87][88] and video [83,88,156]. Leveraging the improved connectivity and ubiquity of smartphones, some authors offer access to entire online libraries of learning materials [127,167]; others utilize in-app prompting as intervention techniques, e.g., sending reminders to use the app [87,103,104,118,159], motivational messages [70] or messages from the therapist [90,163].…”
Section: Coverage Of Technical Dimensionsmentioning
confidence: 99%